2015
DOI: 10.1189/jlb.4a0715-309rr
|View full text |Cite
|
Sign up to set email alerts
|

Host lung immunity is severely compromised during tropical pulmonary eosinophilia: role of lung eosinophils and macrophages

Abstract: Eosinophils play a central role in the pathogenesis of tropical pulmonary eosinophilia, a rare, but fatal, manifestation of filariasis. However, no exhaustive study has been done to identify the genes and proteins of eosinophils involved in the pathogenesis of tropical pulmonary eosinophilia. In the present study, we established a mouse model of tropical pulmonary eosinophilia that mimicked filarial manifestations of human tropical pulmonary eosinophilia pathogenesis and used flow cytometry-assisted cell sorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 63 publications
1
61
0
Order By: Relevance
“…However, the effects of filarial worms on various subsets of host DCs during the very early stages of infection remain obscure. Recently, using a mouse model of TPE, we showed that the pathogenesis of TPE is characterized by functional impairment of alveolar macrophages (AMs), alternative activation of lung macrophages, and upregulation of antiapoptotic genes by eosinophils, which led to severe lung inflammation and compromised host lung immunity (11). Extrapolating our findings even further, in the present study, we infected BALB/c mice with infective Bm-L3 and studied the effect of this infection on flow-sorted DC subsets present in the secondary lymphoid organs of mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the effects of filarial worms on various subsets of host DCs during the very early stages of infection remain obscure. Recently, using a mouse model of TPE, we showed that the pathogenesis of TPE is characterized by functional impairment of alveolar macrophages (AMs), alternative activation of lung macrophages, and upregulation of antiapoptotic genes by eosinophils, which led to severe lung inflammation and compromised host lung immunity (11). Extrapolating our findings even further, in the present study, we infected BALB/c mice with infective Bm-L3 and studied the effect of this infection on flow-sorted DC subsets present in the secondary lymphoid organs of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, single-cell suspensions of spleens from at least 6 to 8 identically treated mice were pooled, and CD11c-positive cells were enriched using CD11c beads, as described above. Sorting was carried out using a high-speed FACS Aria flow cytometer (BD Biosciences) fitted with a 70-m nozzle, as described recently (11,67). After sorting, the sorted cells were subjected to analysis to ascertain their purity, and a small fraction was used to prepare cytospins (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations